2008
DOI: 10.1016/j.cattod.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Cu/ZnO catalysts derived from different precursors as a function of aging

Abstract: Structural modifications of Cu/ZnO catalysts for methanol steam reforming (MSR) as a function of precipitate aging in catalysts preparation process has been investigated comparatively. Freshly precipitated Cu,Zn-hydroxycarbonate (HC) and Cu,Zn-hydroxynitrate (HN) were aged in their mother liquor for a period of 120 min followed by washing, drying, calcination and reduction. Pronounced effect of aging was found for aged HC precipitates while no significant effect of aging was observed for aged HN solids. The bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…[24][25][26] Günter et al reported that such strong interaction causes strained Cu lattices, and the Cu microstrain is closely related to the Cu-ZnO activities in methanol synthesis and methanol steam reforming. [26][27][28][29] It is apparent that this established knowledge will be beneficial to the current study of glycerol hydrogenolysis and the specific emphasis in this work on elucidating the structure effects on the performance of Cu-ZnO catalysts and the underlying reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Günter et al reported that such strong interaction causes strained Cu lattices, and the Cu microstrain is closely related to the Cu-ZnO activities in methanol synthesis and methanol steam reforming. [26][27][28][29] It is apparent that this established knowledge will be beneficial to the current study of glycerol hydrogenolysis and the specific emphasis in this work on elucidating the structure effects on the performance of Cu-ZnO catalysts and the underlying reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, copper based catalysts have received considerable attention for H 2 production by steam reforming of methanol (SRM) or oxidative steam reforming of methanol (OSRM) [3][4][5][6][7]. However, in recent times gold-base catalysts have been extensively studied in connection with the advancement in fuel cell technology and related hydrogen fuel processing.…”
Section: Introductionmentioning
confidence: 99%
“…Within 240-260°C, Cu/ZnO displayed higher H 2 selectivities (*60%) than Cu/Zn/Al 2 O 3 (*50%), Cu/Zn/MgO (*40%), and Cu/Zn/ZrO 2 (*40%). Presumably, Cu/ZnO and Cu/Zn/Al 2 O 3 might have a larger amount of active centers for SRM, which locate on the Cu-Zn interface [28,29], than other promoted catalysts for H 2 production. Cu/Zn/MgO appeared to have the same catalytic behavior as Cu/ZnO and Cu/Zn/Al 2 O 3 with a lower start-up temperature.…”
Section: Discussionmentioning
confidence: 97%